Long day's journey into night [videorecording (DVD)] - Bi, Gan, 1989-; Tang, Wei, 1979-; Huang, Jue, 1975-; Zhang, Aijia, 1953- (Kino Lorber, 2019)
A man returns to Kaili, Guizhou, the hometown from which he fled many years before. Back for his father's funeral, he recalls the death of an old friend, and searches for a lost love who continues to haunt him